(untitled) (KYAMC Journal, 2019)
Background: Extended Spectrum Beta-Lactamase (ESBL) can cause infections, such as kidney infections, wound infections or in severe cases, blood infection. If a patient is prone to infection and the infection is caused by ESBLs, it can be more difficult to treat, because many of the commonly used antibiotics will not work against ESBLs. Materials and Method: This descriptive cross-sectional study was carried out to evaluate samples submitted for culture and sensitivity at Clinical Laboratory of North Bengal Medical College Hospital, Sirajganj the general objective identify the causative organisms and their antimicrobial resistance pattern. Results: Majority of subjects (37.5%) were from 46-60 years age group. ESBL resistance was significantly related with age groups and educational status. Resistance was not related with gender distribution, occupation, family size and yearly family income. Detection rate of ESBL production among Pseudomonas spp were (91.67 %), followed by Klebsiella spp. (83.33 %), Proteus spp. (69.49%), Esch. Coli (64.42 %) and others (82.35 %). Aztreonam, Ampicillin, Amoxyclave and Piperacillin were more resistant antibiotics against ESBL producing organisms. Conclusion: ESBL antibiotic resistance pattern should be determined in chronic Gram negative infection for effective treatment. KYAMC Journal Vol. 10, No.-1, April 2019, Page 7-12